From diaspora TV to social media : Korean TV dramas in America - Lee, Sangjoon (University of Michigan Press, 2020)
Korean TV dramas debuted on the airwaves of the U.S. in 1975, exclusively for overseas Korean communities in an entry-port city, Los Angeles. They then began circulating through two Korean diasporic media outlets: Korean-language TV stations and video rental stores. The latter were in Koreatowns in major metropolitan cities, such as Los Angeles, New York, Chicago, San Francisco, Washington D.C., and Atlanta. This well-maintained, two-channel system has, however, considerably frayed in the new millennium as U.S. consumption patterns of Korean dramas expeditiously migrate toward video streaming websites like YouTube, Hulu, and Netflix, and online-based fan communities whose ethnic identity is not necessarily Korean. Since the early 2000s, myriad illegal web services and social media networks have provided, shared, and disseminated Korean TV dramas, along with K-pop, to the mainstream users/viewers in the United States that eventually resulted in the first legitimate video streaming service DramaFever.com. The aim of this chapter is to historicize and analyze the distribution, circulation, and reception of Korean TV dramas in the United States, from diasporic TV, exclusively for Korean immigrants, to the mainstream media market, in the age of social media.